STUDI ETNOGRAFI : KONSEP TRANSFROMASI GEOMETRI KERIS KYAI TENGARA - Annastiar, Sabrina; Chandra, Fabira; Muzaiyanah, Ufiq; Arfinanti, Nurul; Suparni, Suparni (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
This research is motivated by the existence of a link between cultural elements that can represent mathematical objects as an alternative learning media in mathematics material. Indonesia has a variety of cultural heritages, one of which is Keris. This culture can be used to explore mathematical concepts to bring mathematics closer to cultural elements; it can also be used in the context of school learning. The main objective of this study is to examine the concept of geometric transformation contained in the Keris motif, the Keris, which is the main object in this study, namely